Analisis Kelayakan Investasi Menggunakan Metode NPV di KUD Sinamar Sakato - Fendri Amir; Tri Gamela Saldy (Journals Mining Engineering : Bina Tambang, 2022)
Industrial development in Indonesia is very rapid, especially in the mining sector, where Indonesia is a country with very rich mining sector natural resources, so that it is in the spotlight of investors to establish mining sector companies. As an industry that is currently developing, it should be noted that setting up a mining company requires a lot of money or capital. Even so, the profits to be obtained are also very large which makes the mining sector industry in great demand by investors. This study uses the NPV method to see whether the investment is feasible or not. This project is said to be feasible because the NPV value obtained is IDR 496.473.602.258,14 or greater than 0. Keyword:  Feasible, NPV